A Survey of the Practices, Procedures, and Techniques in Senior Secondary School Chemistry Teaching Laboratories - Ram Babu Pareek (International Journal of Chemistry Education Research, 2022)
A survey was conducted in various senior secondary schools of Rajasthan State  that teach chemistry at senior secondary level and conducts chemistry practicals in  laboratories in the India. The data include results from over 27 schools, describes the current practices, procedures and techniques used   at these schools, and discusses the statistical results such as the adaptability of  laboratories performed, the chemical techniques applied, the instrumentation/chemicals available, the laboratory equipment used, the chemistry practicals covered, the way they conducted and performed . The results provide a “snapshot” of the current state of the senior secondary school laboratory teaching chemistry practicals.